2008
DOI: 10.1007/s00449-008-0234-4
|View full text |Cite
|
Sign up to set email alerts
|

Cole–Cole, linear and multivariate modeling of capacitance data for on-line monitoring of biomass

Abstract: This work evaluates three techniques of calibrating capacitance (dielectric) spectrometers used for on-line monitoring of biomass: modeling of cell properties using the theoretical Cole-Cole equation, linear regression of dual-frequency capacitance measurements on biomass concentration, and multivariate (PLS) modeling of scanning dielectric spectra. The performance and robustness of each technique is assessed during a sequence of validation batches in two experimental settings of differing signal noise. In mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 43 publications
1
52
0
Order By: Relevance
“…Even more recently, yeast cultures were analyzed using Cole-Cole, linear, and multivariate statistical regression analysis, with the authors finding the multivariate statistical method to provide the most satisfactory results. 38 Also in yeast, Maskow et al 33 observed a departure from a linear response between permittivity and biomass that arose during changes in intracellular lipid formation. They further analyzed the changes in the f c and a values that occurred during this time, and found they correlated well with the physiological changes during the culture.…”
Section: Eðf þ ¼mentioning
confidence: 98%
“…Even more recently, yeast cultures were analyzed using Cole-Cole, linear, and multivariate statistical regression analysis, with the authors finding the multivariate statistical method to provide the most satisfactory results. 38 Also in yeast, Maskow et al 33 observed a departure from a linear response between permittivity and biomass that arose during changes in intracellular lipid formation. They further analyzed the changes in the f c and a values that occurred during this time, and found they correlated well with the physiological changes during the culture.…”
Section: Eðf þ ¼mentioning
confidence: 98%
“…For example, in vitro impedance measurements have been shown to detect cell proliferation and cell-drug interaction 12 , quantify biomass in suspensions 11,13 and create two-dimensional images of cell migration 14 . Much of this work utilizes the electrical 'signature' of the cell membrane: a well-functioning cell membrane is relatively impermeable and thus behaves like a capacitor in the presence of electric current [9][10][11]13,15 . Cell damage or death results in a loss of membrane structure and integrity, allowing ions and current to pass through the membrane.…”
mentioning
confidence: 99%
“…The fitting algorithm was described in details by Dabros et al [26]. The parameters (DC and f C ) of the fitted model were calculated by the software.…”
Section: Dielectric Spectroscopy and Cole-cole Model Fittingmentioning
confidence: 99%